POLA KOMUNIKASI ORGANISASI UNIT TERMINAL INSPECTIONS SERVICE (TIS) DALAM PENANGANAN TEMUAN KERUSAKAN FASILITAS PENUNJANG PELAYANAN DI TERMINAL BANDARA SULTAN SYARIF KASIM II PEKANBARU - Fukuhara, Shafira Keiko; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Sultan Syarif Kasim International Airport in Pekanbaru City, Riau Province has a very important role in supporting the flow of air traffic between Indonesian regions and the flow of international flight traffic. The high number of users at SSKII Airport from time to time means that service support facilities at the airport terminal are increasingly being improved in order to maintain the comfort of users. However, unfortunately, damage to facilities is still often found, which means that the TIS unit as the person responsible for the facility must immediately deal with the damage so as not to disturb the comfort of users. . This research aims to analyze organizational communication patterns and communication media used by the TIS unit, as well as communication obstacles experienced in dealing with findings of damage to service support facilities at the Sultan Syarif Kasim II Airport terminal in Pekanbaru. This research uses a qualitative research method with a descriptive approach. The subjects in this research were nine people located at Sultan Syarif Kasim II Airport, Pekanbaru. Data collection was carried out through interviews, observation and documentation. Data analysis techniques by collecting data, reducing data, presenting data, and drawing conclusions. Apart from that, data validity checking techniques use source triangulation and time triangulation. The research results show that the Terminal Inspections Service (TIS) Unit uses a star communication pattern (all channels) and a chain communication pattern in handling findings of damage to service support facilities at the Sultan Syarif Kasim II Airport terminal in Pekanbaru. The star communication pattern is used within (internal) the TIS unit when coordinating with fellow Officers and Supervisors, while the chain communication pattern is used outside the TIS unit when coordinating with the Assistant Manager and the unit responsible for handling findings of damage to facilities at the airport terminal. Keywords: Organizational Communication Patterns, Communication Media, Communication Obstacles, Sultan Syarif II Airport Pekanbaru, Terminal Inspections Service Unit